Wajah Pluralis, Feminis, dan Puitis dalam Tafsir Karya Djohan Effendi - Mukhamad Saifunnuha (AL QUDS : Jurnal Studi Alquran dan Hadis, 2020)
Pluralist, Feminist, and Poetic Faces in Djohan Effendi’s TafsirThe books of tafsir, which originally appeared in the Middle East, spawn extensively tomany countriesincluding Indonesia. One of the contemporary Indonesian tafsirbooks is ‘Pesan-Pesan al-Qur’an’ by Djohan Effendi, whichdeserves to receive researchers’ and academics’ attention because of its uniqueness. Hence, this research aims to study and analyze this tafsirbook in terms ofbothmethodological aspect and book’s contents. The author uses the ‘Four Methods’ theory from Al-Farmawiy and also IslahGusmian’s concept for the methodological analysis. Finally, by some analysis and discussion, this research finds that Djohan’stafsir uses the ijmali methodcombined with the thematic method. While in the contents of the book, this tafsir has 3 major tendencies, namely pluralist, feminist, and poetic.